Grant awarded by the Cyprus Research Promotion Foundation (POST-DOC/0916/0237) - Kapnisis, Konstantinos (My University, 2026)
Ranked 1st among 193 submitted proposals Duration: 2018-2020 Budget: €159,999 http://www.paideia-news.com/index.php?id=109&hid=30077&url=Το-ΤΕΠΑΚ-εξασφάλισε-την-1η-θέση-στην-Κύπρο-στο-ερευνητικό-πρόγραμμα-«ΔΙΔΑΚΤΩΡ»
Keywords: Sciences